Generalized knockout tournament seedings - Karpov, A. (International Journal of Computer Science in Sport, 2018)
Generalized knockout tournament seedings for an arbitrary number of participants in one match are designed. Several properties of knockout tournament seedings are investigated. Enumeration results for knockout tournament seedings with different properties are obtained. Several new generalized knockout tournaments seedings are proposed and justified by a set of properties.